EXPRESSIONS SONGYE – SONGIE EN RÉPUBLIQUE DÉMOCRATIQUE DU CONGO - Claudine NTOMBE Kapenga; Gédéon MPOSHI Kyungu (IJRDO- Journal of Educational Research, 2025)
The use of Songye words during a speech or during a family interview would be learning experience for Songye youth. According to the manner of Basongye in general, there is the way in which the months, days, hours, fingers, others were colled, … and ther meaning, which would send us to make available to the Ba – songye these some Songye expressions like “the mounths of the year, the days of the week, the hours and the meaning of fingers in Kisongye” online as there is technological development (NTIC) and give a history for Basongye. The Kisongye language can semm difficult to us and disappear if it is simply dedicated to oraly. This time it remains know among Songye only, because it is a mother tongue (dialect or idiom) learned by word of ear, from generation to generation. Therefore, to our knowledge, we must ensure that there are many hard and electronic works put online and in libraries facilitating the learning and recall of Songye words and expressions (in Kisongye) our only to our women and children, but to all readers from various provinces and why not in the world. After our moment of study and research, we learned that Songye youth and any category of the Songye population find it difficult to start a debate in Kisongye and reach endless ends without using French words in their speech while our Kisongye language is rich in words and verbs